(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In the development and employment process of Wave Energy Conversion Systems (WECs), it is crucial to understand the existing potential and achievable economic benefits to attract the commercial or governmental interest and use the funding sources as effectively as possible. Wave energy harvesting has significant potential for clean electric production but is not mature yet due to being in the technological development stage and high costs. Therefore, feasibility studies predicting the potential energy production and costs need to be conducted preliminarily and continuously to promote the efforts in this field. In this study, a particular interest has been put to Türkiye by conducting a resource feasibility study (i.e. from power production aspect) for WECs deployment in the Black Sea Basin where Türkiye holds approximately 1700 km of coastline. Five different locations along the seacoast—Istanbul, Filyos, Sinop, Samsun, and Hopa—have been selected to capture the potential of different parts through the whole coastline. From the adopted wave data, sea state matrices of those selected locations between the years 2010 and 2020 have been obtained. Here, two different WECs have been selected. The information about the power production of each device has been collected from their developers. By the help of annual energy production (AEP) calculations for each year-device-location configuration, the viability and the potential of WECs in the Black Sea for Türkiye have been studied. These results will help to shape the future expectations for WECs deployments in the Black Sea.